(untitled) (Research, Society and Development, 2022)
The resistance developed by Mycobacterium tuberculosis to the drugs used in the treatment constitutes a major public health problem in several countries and is considered one of the main obstacles to the control of tuberculosis worldwide. Thus, the objective was to analyze the factors associated with the prevalence of tuberculosis resistant to multiple drugs, through an integrative literature review of the last 5 years, using the LILACS, MEDLINE and SCIELO databases, which make up the Virtual Health Library. The result was 726 articles, of which 49 were pre-selected to be read in full, resulting in 14 approved articles. It was observed that many of the accepted articles had as place of study the Asian continent and South America. Therefore, strategies for controlling MDR-TB should emphasize the effective implementation of the strategy for continuous surveillance of drug resistance and patient-centered approaches.